(3oZQQ GdMce hoOQQ Gdcdes - (3CHhGdaJM fGUM GdOjf YHO GdhGMO Hf eMeO Hf YHO GdhGMO GdJejej GdBeOjs; (3CHhGdMSf Ydj Hf CHj WGdH Hf YHO GdeWdH,J (B40 (3g` s
(3ChdgG (B:s
(3hHYO aEf GdPj MOGfj Ydi JNUjUg ahGFO s
(3BNQgG (B:s
(3Ef YOdhG cTahG, hEf McehG CSQahG, fbhT NhGJje CejQ GdeDefjf Ydj QVj Gddg Yfg Je s
(3JJab aj ChdgG hBNQgG eY GdfSNI GdChdi eY GNJdGa aj HYV GdCdaGXs
(3hHgG fXGe GdJYbjHIs
(3ef cdGe GdEeGe Ydj Hf CHj WGdH QVj Gddg Yfgs
(3GdeJhai (B40 (3g` s
(3fSNI QGHYI s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs